The Clash of Civilizations in the Syrian Crisis //El choque de civilizaciones en la crisis Siria - Mohammadi, Shoayb; Butenko, Vladyslav; Ghadbeigi, Zohreh; Ahangaran, Masoumeh (Revista de la Universidad del Zulia, 2020)
The Syrian crisis may be the beginning of a new conflict of civilizations. Ethnic and religious pluralism is clearly evident in this country: Muslims (Sunnis, Druze, Alawites, Shiites and Ismailis); Christians (Orthodox, Catholics, Maronites, Protestants) and Turkmen and Kurdish ethnic minorities. The Syrian crisis of 2011 seemed to go against the ruling elite (Alawis). With the escalation of the conflict, the country gradually became the scene of a civil war characterized by international dimensions. In this way, the conflict became a multilateral battle in which, on the one hand, the participants in it were the local element in the form of the government of Bashar al-Assad and extremist terrorist groups such as Jabhat al-Nusra, ISIL and Ahrar al-Sham; and on the other hand, the United States and its European allies, Saudi Arabia and some States of the Persian Gulf; and Iran and the axis of resistance, as well as Russia and China. Due to the presence of diverse cultures and religions, it appears that this will make the Syrian crisis a prelude to a renewed clash of civilizations. This research seeks to answer these questions: What are the basic propositions of the theory of the clash of civilizations and how is it represented in the Syrian crisis? Since, according to Samuel Huntington, the main sources of the clash of civilizations are the foundation of civilizations, religious and cultural antecedents, and cultural and religious identities. Consequently, they are expressions of the clash of civilizations: the war on terrorism, the Syrian crisis, the rise of ISIL and the presence of US military and international interventions, the competition of regional and transnational powers. Resumen La crisis Siria puede ser el comienzo de un nuevo conflicto de civilizaciones. El pluralismo étnico y religioso es claramente evidente en este país: Musulmanes (sunitas, drusos, alauitas, chiítas e ismaelitas); Cristianos (ortodoxos, católicos, maronitas, protestantes) y minorías étnicas turcomanas y kurdas. La crisis Siria de 2011 parecía ir en contra de la élite gobernante (alauita). Con la escalada del conflicto, el país se convirtió paulatinamente en escenario de una guerra civil caracterizada con dimensiones internacionales. De esta manera, el conflicto se convirtió en una batalla multilateral en la que, por un lado, los participantes en él eran el elemento local en la forma del gobierno de Bashar al-Assad y grupos terroristas extremistas como Jabhat al-Nusra, ISIL y Ahrar al- Sham; y por otro lado, Estados Unidos y sus aliados europeos, Arabia Saudita y algunos Estados del Golfo Pérsico; e Irán y el eje de la resistencia, así como Rusia y China. Debido a la presencia de diversas culturas y religiones, parece que esto hará de la crisis Siria un preludio de un renovado choque de civilizaciones. La presente investigación busca dar respuesta a estas preguntas: ¿Cuáles son las proposiciones básicas de la teoría del choque de civilizaciones y cómo se representa en la crisis Siria? Dado que, según Samuel Huntington, la principal fuente del choque de civilizaciones son la fundación de civilizaciones, los antecedentes religiosos y culturales y las identidades culturales y religiosas. En consecuencia, son expresiones del choque de civilizaciones: la guerra contra el terrorismo, la crisis Siria, el surgimiento del EIIL y la presencia de las intervenciones militares e internacionales de Estados Unidos, la competencia de potencias regionales y transnacionales.